Feasibility of elective neck irradiation in treating node-negative nasopharyngeal carcinoma patients: a meta-analysis - Zhou, Jianfeng; Wang, Hongyong (Frontiers in Oncology, 2025)
PurposeIntensity modulated radiation therapy (IMRT) has replaced conventional two-dimensional radiation therapy as the mainstream radiation therapy for nasopharyngeal carcinoma. However, side effects continue to be a significant concern during the radiotherapy process for nasopharyngeal carcinoma patients. The recognized target area for cervical prophylaxis in nasopharyngeal carcinoma is whole neck irradiation (WNI), Currently, some studies have confirmed that upper neck irradiation (UNI) may be feasible as a preventive measure for NPC patients with negative neck lymph nodes. This meta-analysis aimed to comprehensively investigate and compare the efficacy of selective UNI and WNI in improving survival outcomes and regional control in patients with lymph node-negative NPC.Materials and methodsA systematic search was conducted in PubMed, EMBASE, The Cochrane Library, and CNKI from inception to October 27, 2023, using a combination of Medical Subject Headings (MeSH) terms and free-text keywords related to “nasopharyngeal carcinoma,” “lymph node negative,” and “neck irradiation.” The titles and abstracts of the retrieved articles were reviewed.ResultsOur meta-analysis of 11 studies revealed no significant differences in overall survival (OS), disease-free survival (DFS), distant metastasis-free survival (DMFS), or lymph node recurrence between the UNI and WNI groups for patients with cervical lymph node-negative nasopharyngeal carcinoma. These findings suggest that UNI is a safe and feasible treatment option for this patient population.ConclusionUNI is a safe and feasible option for nasopharyngeal carcinoma patients with negative cervical lymph nodes or only retropharyngeal lymph node (RLN) metastases. UNI may reduce the radiation dose to normal tissues, potentially decreasing long-term adverse effects and improving quality of life.